P013 Porphyromonas gingivalis infection linked to ra onset and ANTI TNF alpha treatment non-response. (21st February 2018) - Jenning, M; Marklein, B; Ytterberg, Y; Catarina, A; Schaardenburg, D; Bürmester, G; Skriner, K
Abstract : Introduction: Differences in enzymatic activity and pathogenic impact of Porphyromonas gingivalis ( P.g. ) peptidylarginine deiminase (PPAD) for development of RA have been published, confounded by different PPAD variations and methods used. Objectives: Enzymatic active PPAD isolated from an RA patient (RA-PPAD) was first time linked to citrullination of RA autoantigens, diagnosis, therapy response and RA-onset. Methods: Recombinant RA-PPAD cloned, verified by DNA sequencing and expressed in Escherichia coli and purified. RA-PPAD and its enzymatic activity was analysed using 2D-Elektrophoresis, mass spectrometry (MS), immunoblot and ELISA. Results: RA-PPAD autocitrullinates amino acid position 63 (aa63 ) and exhibits so far two new amino acid mutations aa73 F to L and aa447 E to V. Anti-citrullinated RA-PPAD antibodies were detected in 38% (n=36) of patients with RA, but were absent in Systemic lupus erythematosus (n=30), Osteoarthritis (n=36) and control sera (n=23). Twenty percent of RA patients (n=30) showed an increase in antibody-titre against citrullinated RA-PPAD after RA onset. High antibody titre against the cit-PPAD-peptide of 15aa (CPP) derived from the autocitrullination site (R63 ) correlates with TNFα-inhibitor (TBA) non-response (n=61). Anti-CPP levels correlate with DAS28, rheumatoid factor, α-CCP 2 levels and increase with age. RA-PPAD is able to citrullinate internal arginines in fibrinogen, vimentin, hnRNP-A2/B1 and histone H1. This internal citrullination-sites are recognised by RA sera and able to bind HLA401. Conclusions: Failure of P.g. clearance in RA patients may lead to excessive exposure of citrullinated self-antigens and bacterial antigens inducing immune-mimicry. P.g. infection can be linked to RA and its correlation to TBA non-response leads to the suggestion to clear P.g infection before α-TNF treatment. Disclosure of interest: None declared